The effectiveness of Using Flipped Classroom Strategy in Developing Algebraic Thinking Skills of Secondary Stage Female Students - Al- Otaibi, Haifa Saad; Iraqi, Al- Said Mahmoud (Journal of Educational and Psychological Sciences, 2019)
The aim of the study was to identify The effectiveness of the use of The Flipped Classroom Strategy in The Development of The Algebraic Thinking Skills of high School students and to achieve the objective of the study, the symbol of the study consisted of (56)female Secondary school students in the Secondary stage randomly divided into two groups one which consisted of (29) female students who study the Unit of "Sequences and Series" using Flipped Classroom, in addition the other students were taught the same topics in the usual way from (27) female students. In addition, the measurement test was conducted in the form of the algebraic thinking skill and the preparation of the teacher's guide in the light of the flipping the classroom using "Articulate Storylines (3)", the use of the Educational Platform "Edmodo", and the preparation guide of the activities for the students . The data were processed statistically. The results indicated a statistically Significant differences (0.05) Between that mean scores of the experimental and control groups in the skill of exploring relationships and algebraic functions in the favor of the group’s experimental students attributed To the use of the flipped classroom strategy, and no statistically significant differences (0.50) Between that mean scores of the experimental and control groups in the skill of (patterns and algebraic generalization, use representations and algebraic symbols), and In general there was no statistically significant differences between (0.05) between the average scores of the female students in the experimental and control groups in the post- application to test algebraic thinking skills in the total score. Based on the Findings a number of recommendations and proposals were presented that could contribute to the development and enrichment of mathematics education.
Keywords: the flipped classroom; algebraic thinking